Spectrophotometric Determination of Praseodymium(III) After Extraction with 8-Quinolinol and its Halogen Derivatives into Molten Naphthalene - Vyas, P.C.; Mittal, V.P. (Asian Journal of Chemistry, 2010)
The sensitive method "solid-liquid separation after liquid-liquid extraction" has been employed for collecting traces of Pr(III) from aqueous solution by precipitation with 8-quinolinol, 5-chloro-8-quinolinol and 5-chloro-7-iodo-8-quinolinol into molten naphthalene. The extraction behaviour of praseodymium(III) complexes with these reagents have been discussed in terms of various parameters like molar absorptivities, linear calibration ranges for Beer's law, Sandell sensitivities and standard mean deviations.